The Role of the Cimahi Police Binmas Unit in Preventing Drug Abuse Among Youth - Costazolanitova, Briyan (Police Studies Review, 2024)
Among teens is very easy to be influenced to the abuse of drugs, as in the case of this adolescent is someone children who experience changes in behaviour are fast in all aspect, intelligence, feeling, concerning changes in the body, attitude and mental personality. These teens tend to be easy affected because not stable emotions that tend to lead to behaviour that is less good end in her many changes.The theory that is used in the research is that the theory of communication, Theory of Management and also using Analysis SWOT concept that used concept of Narcotics and Concepts Bhabinkamtibmas. Focus study that research take on the thesis of this is the role of Unit Binmas Police Cimahi. Sources are used is a source of primary and secondary. Mechanical collection of data by interviews, observation, study document. As well as the validity of the data using the source. The results finding were obtained by the author for the study is the role of Unit Binmas Police Cimahi in preventing the abuse of drugs among adolescents is still not optimal to perform communication persuasive, coordinating and working together with agencies other as well as the empowerment potential of the community to participate actively in prenventing the misuse of drugs in the teens. In order to increase the role of Unit Binmas Police Cimahi in preventing the misuse of drugs in the teens needed capability communications personel were steady, the funcionts of management optimal start of the planning, organizing, actuating and controlling. The results of the study, the authors put forward some suggestions, among other personnel Unit Binmas Police Cimahi develop targeted guidance and counselling related to drugs in shools at the level of junior high and elementary school, and the releted ability of personnel in communications persuasion concerening the prevention of abuse of drugs are still minimal, preferably Police engage personnel in training at the level pf Police as well as the implementation of the FGD were conducted by the Binmas Unit, Satresnarkoba and teen psychologist.